Comparison of some Macro and Micro Mutrients in Tomato Fruits Exported Abroad from Turkey According to the Growth Conditions - ÖZYİĞİT, İBRAHİM İLKER (My University, 2022)
Tomato is one of the most widely cultivated (conventionally, greenhouse or soilless agriculture) and important agricultural products among the members of the Solanaceae family as well as all vegetables. It also plays a significant role in healthy dietary nutrition with its ingredients such as lycopene which gives its natural color and is an abundant free radical scavenger, anthocyanin and vitamin contents. Soil properties and fertilization is a significant parameter for yield, mineral content and fruit quality of tomato. Turkey is one of the largest tomato producers in the world after China, India and the USA. Aim of this study aim is to determine the some macro and micro elements of edible tomato fruits from various origins of a significant producer country (Turkey) and also to compare the differences with tomatoes grown with different methods both in Turkey and other tomato producing countries. One of the most important steps in inductively coupled plasma mass spectroscopy (ICP-MS) technology is sample preparation. For the parts of each plant sample, the EPA 3051A analytical method was applied using nitric acid in Teflon cells. The prepared samples were thawed in a CEM Mars 5 microwave. The concentrations (in mg kg-1 ) of, Ca, Cu, Fe, K, Mg, Mn, Na and Zn in the dried samples have been determined by employing ICP- MS (Agilent 7700 Series). The order of locations with respect to the element concentrations from the highest to the lowest is Mediterranean and Southeastern Anatolia Regions>Marmara Region>Aegean Region>West part of Central Anatolia Region. Based on available elemental concentrations from the study conducted in major Turkish tomato production centers, we can extrapolate ideas about the necessary fertilization programs from mineral nutrients contents of tomato fruits. Statistically significant differences were obtained in mineral nutrients from greenhouse and field samples except for Mg, Mn, and Zn due to the fact that intensive regimes of production and fertilization were practiced in greenhouses. In terms of mineral nutrient content, tomato samples collected from different parts of Turkey showed close similarity with previous studies except for K content. K content was detected to be low in comparison with previous results. The K fertilization may have been ignored in the major tomato production sites of Turkey in contrast to other parts of the world. Keywords: Solanum lycopersicum L., Nutriens, Field, Greenhouse, ICPMS, Bioaccumulation
Keywords: Temel Bilimler; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; Multidisipliner; Multidisciplinary; Solanum lycopersicum L.; Nutriens; Field; Greenhouse; ICPMS; Bioaccumulation